SPIKELET NUTRIENTS OF RICE AND THEIR RELATION TO GLUME BLIGHT - B. M. SINGH, S. K. SUGHA AND (Indian Phytopathology, 2002)
Spore germination and germ tube elongation of Phyllosticta glumarum were stimulated by extracts and exudates of spikelets of different rice cvs. Exudates from susceptible rice cvs (Himdhan, IRÂ·S79) stimulated spore germination and germ tube elongation to a greater extent than exudates from resistant cvs (Mushkan, Norin-Id). Exudates from anthers caused more stimulation in spore germination and germ tube elongation as compared to glumes, whole spikelets or ovaries. Spikelet exudates from susceptible rice cvs were found to contain higher concentration of total sugars, amino acid than resistant cvs. No appreciable difference in the phenolic compounds was detected between the susceptible and resistant rice cvs.